A Post-Traumatic Growth Perspective on PTSD: Implications for Those Who Have Served and Their Partners. (15th August 2022) - Norris, Deborah; Smith Evans, Kimberley; Cramm, Heidi; Tam-Seto, Linna
Abstract: Research emphasizing the negative psychosocial impacts of service-related post-traumatic stress disorder (PTSD) for military members, veterans, and their families is well established. Post-traumatic growth (PTG), positive psychological change resulting from managing adverse life events and situations, is an alternate outcome considered in research focusing on the impacts of serious illness and other life-altering circumstances on families. Little is known, however, about the processes that create and sustain PTG within military and veteran family systems. This paper will review conceptualizations of PTG and consider its relevance as a construct for analysis of outcomes related to the experiences of partners of military members and veterans living with PTSD and other operational stress injuries.